The Association of Scoliosis and NSD1 Gene Deletion in Sotos Syndrome Patients. Issue 13 (1st July 2021) - Machida, Masafumi; Katoh, Hiroyuki; Machida, Masayoshi; Miyake, Atsushi; Taira, Katsuaki; Ohashi, Hirofumi
Abstract : Study Design: A retrospective comparative study. Objective: The aim of this study was to examine the NSD1 abnormalities in patients diagnosed with Sotos syndrome and its correlation with the presence, severity, and progression of associated scoliosis. Summary of Background Data: Scoliosis has been reported in approximately 30% of patients diagnosed with Sotos syndrome, a genetic disorder characterized by a distinctive facial appearance, learning disability, and overgrowth. Sotos syndrome is mainly attributed to NSD1 haploinsufficiency, but with ethnical differences in genetic profile: NSD1 microdeletions are frequently identified in Japanese Sotos patients whereas intragenic mutations are more frequently found in non-Japanese patients. Although possible genotype–phenotype correlations have been proposed, the genotype of Sotos syndrome patients suffering from scoliosis has not been examined. Methods: The medical records and spinal radiographs of 63 consecutive Sotos syndrome patients at a single center were reviewed. Fluorescent in situ hybridization or microarray comparative genomic hybridization and DNA sequencing or multiplex ligation-dependent probe amplification were performed to detect 5q35 microdeletion involving the NSD1 gene and intragenic mutations of the NSD1 gene, respectively. The phenotypes of all cases and radiological assessments for the presence and progression of scoliosis were studied. Results: NSD1 abnormalities were identified in 55 patients (87%): microdeletion in 34 patients (54%) and intragenic mutation in 22 patients (33%). Scoliosis was observed in 26 patients (41%), with a significantly higher ratio of microdeletions than mutations. The 10 patients with progressive scoliosis all had NSD1 microdeletions. Conclusion: Scoliosis was a common phenotypical trait in children with Sotos syndrome and its presence as well as progression were higher in cases with NSD1 microdeletions. Although all Sotos syndrome patients should be monitored for scoliosis, clinicians should be made aware that patients with NSD1 microdeletions have a higher probability of scoliosis development and progression that may require early intervention. Level of Evidence: 3 Abstract : A single-center review of 63 Japanese Sotos syndrome patients revealed NSD1 microdeletions in 54% and NSD1 intragenic mutations in 33% of patients. Scoliosis was observed in 41% of patients, with higher presence and progression of scoliosis found in cases with NSD1 microdeletions compared to cases with NSD1 intragenic mutations.